Promoting PT. Essentra’s Cigarette Filters through a Marketing Booklet - Monica Chiesa Adrian (Kata Kita: Journal of Language, Literature, and Teaching, 2019)
PT. Essentra is a manufacturer located in Sidoarjo which produces cigarette filters and tear tape for cigarette packaging. The main problem that happened in the company is the ineffective way to introduce and promote company’s product as the marketing team only uses product presentation slide as their tool. While giving product presentation, customers often get bored as it covers lot of explanation and take long time to finish one presentation. Therefore, the solution I offered for the company is to make a marketing booklet. This marketing booklet consists of information regarding the company and explanation of cigarette filter products along with the benefits that customers will have. This solution will help PT. Essentra in promoting its products and fulfill the customers’ request related to a tool for them to review the company’s products. By having this marketing booklet, it can help the company to introduce and promote its products and fulfill the customers’ request of a tool for reviewing the company’s products which PT. Essentra offered. By having this tool, PT. Essentra has additional promotional tool for helping the marketing team as well as the customers. Keywords: Promotional Tool, Unique Selling Point, Marketing Booklet